Identification of Performance Indicators for Small and Medium-Scale Contractors in Indonesia - Ima Fatima; Aisha Fadila Rahmadani; Salma Azzahra (Jurnal Teknik Sipil, 2025)
Abstract Small and medium-scale contractors in Indonesia face significant challenges in performance measurement, as their assessments are often limited to financial metrics and lack a structured system. This study aims to identify key performance indicators (KPIs) relevant to such contractors as an initial step toward developing a Balanced Scorecard-based performance measurement system. Data were collected through questionnaires distributed to 28 respondents from 20 contractor companies in Bandung City. The analysis employed comparative tests to ensure consistency across respondent groups, statistical analysis to evaluate relevance and agreement levels, and the Relative Importance Index (RII) to rank indicators according to their perceived importance. The results identified 20 relevant performance indicators, covering all four Balanced Scorecard perspectives: financial, customer, internal business process, and learning and growth. The top-ranked indicators include service quality, customer retention, project completion timeliness, and corporate image. These findings provide a foundation for designing a comprehensive performance measurement system tailored to small and medium-scale contractors. Furthermore, they highlight the need for future research to validate the indicators with broader samples and to operationalize them into a practical measurement framework that can enhance contractor competitiveness. Keywords : Balanced scorecard, key performance indicator, small and medium-scale contractor